A Novel Missense Mutation in the Endoglin Gene in Hereditary Hemorrhagic Telangiectasia - Yamaguchi, Hiroshi; Azuma, Hiroyuki; Shigekiyo, Toshio; Inoue, Hideo; Saito, Shiro (Thrombosis and Haemostasis, 1997)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder characterized by multisystem vascular dysplasia and recurrent hemorrhage. Recent investigation has mapped one of the responsible genes for HHT to chromosome 9q33-q34; subsequently, nine different mutations have been identified in the endoglin gene, which encodes a transforming growth factor β(TGF-β) binding protein, in nine unrelated families with HHT. We examined the endoglin gene in a Japanese patient with HHT and her family members. Using PCR-SSCP. analysis followed by sequencing, we identified a C to A missense mutation in exon 4 which changed an Ala160 codon(GCT) to an Asp160 codon (GAT). Since this mutation destroys one of three Fnu4H I sites in exon 4, the Fnu4H I digestion patterns of the PCR-amplified exon 4 fragments from each family member were analyzed. In affected members, the restriction patterns were all consistent with a phenotype of HHT. PCR-amplified exon 4 fragments from 150 normal individuals were also analyzed by allele-specific oligonucleotide hybridization analysis. As a result, the mutation was not found in any of them. We conclude that the C to A mutation in exon 4 of the endoglin gene in this proband is responsible for the occurrence of HHT in this family.